THE BENEFITS OF READING IN ENGLISH (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
Improved Language Proficiency: Reading in English enhances vocabulary, grammar, fluency, and comprehension, helping individuals develop stronger language skills.   Cognitive and Mental Benefits: Regular reading promotes cognitive function, including better memory, focus, and critical thinking. It stimulates the brain and encourages the development of problem-solving skills.